Effect of Dexamethasone injection at birth on growth performance of pigs from birth to weaning - Young, M.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 82 litters were used in a 21-day study to evaluate the effect of injecting litters of pigs with dexamethasone within 24 hours of birth on growth rate from birth to weaning. Experimental treatments consisted of an injection of 1 mg dexamethasone solution (2mg/mL, Prolab Ltd, St. Joseph, MO) to all pigs within a litter, while pigs in control litters did not receive a dexamethasone injection. There was no difference in growth rate from birth to weaning between pigs injected with dexamethasone and control pigs. Number of pigs weaned per litter and preweaning mortality were not different. In this study no benefit was observed in growth rate from birth to weaning from injecting whole litters of pigs with 1 mg/pig of dexamethasone within 24 hours of birth.
Keywords: Dexamethasone; Pigs; Growth rate; Swine